2013
DOI: 10.1210/en.2012-1967
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vascular Endothelial Growth Factor in Maintenance of Pregnancy in Mice

Abstract: It is well known that withdrawal of progesterone from the maternal circulation is a critical stimulus to parturition in rodents, such as rats and mice. However, mechanisms that determine the timing of progesterone withdrawal are not completely understood. In the present study, we examined whether the vascular endothelial growth factor (VEGF) system in the corpus luteum (CL) contributes to the regulation of circulating progesterone levels and acts as a determinant of the timing of parturition in mice. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…; Wada et al. ). We found under normal pregnant conditions that obese rats have elevated circulating VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…; Wada et al. ). We found under normal pregnant conditions that obese rats have elevated circulating VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the process of luteal regression occurs in a hypoxic environment, as low oxygen tension stimulates VEGF expression and/or the expression of its receptor through the expression of hypoxia-inducible factor-1 (HIF-1) [55]. Wada et al [56] also observed a reduction of the luteal blood flow at the end of the pregnancy period in mice before any of the structural changes of luteal regression. As hyperthyroid animals undergo an early luteal regression [29], one hypothesis is that a hypoxic environment has already been developed in the corpus luteum of these animals at 19 days of gestation, justifying the higher expression of VEGF and Flk-1 in relation to control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hypothyroid animals, a lowered VEGF immunohistochemical expression at 19 days of gestation could compromise luteal function, as VEGF influences the production and release of progesterone by the corpus luteum [42] and controls its vascular permeability [56]. More research is needed to assess how hypothyroidism affects luteal function to the detriment of the alterations observed in the VEGF expression because this thyroid dysfunction results in abortion in the final third of pregnancy and stillbirth [11].…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelia growth factor (VEGF) is one of the important angiogenic genes that has been implicated in the PTB complication [12][13][14]). In-vivo models show that the VEGF/VEGF receptor system plays an important role in the regulation of circulating progesterone level and attenuation of VEGF signaling at mid pregnancy results in onset of labor and parturition because of a reduction in circulating progesterone levels [15]. Two single-nucleotide polymorphisms (SNPs) in the VEGFA gene (rs699947, rs3025039) have been reported in relation to sPTB [12].…”
Section: Introductionmentioning
confidence: 99%